2007
DOI: 10.1088/0031-9155/52/15/015
|View full text |Cite
|
Sign up to set email alerts
|

Thermal therapy for breast tumors by using a cylindrical ultrasound phased array with multifocus pattern scanning: a preliminary numerical study

Abstract: The purpose of this study is to investigate the feasibility of using a 1 MHz cylindrical ultrasound phased array with multifocus pattern scanning to produce uniform heating for breast tumor thermal therapy. The breast was submerged in water and surrounded by the cylindrical ultrasound phased array. A multifocus pattern was generated and electrically scanned by the phased array to enlarge the treatment lesion in single heating. To prevent overheating normal tissues, a large planning target volume (PTV) would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…For example, simulations of a breast-specific cylindrical ultrasound phased-array were performed on a breast model and initial phantom experiments were completed using a cylindrically mounted single solid transducer that was mechanically rotated. 18,19 The first laterally shooting HIFU transducer system to be used in malignant tissue on a patient 9 was not used beyond the initial feasibility study. A recent report 20 described a laterally shooting 384-element phasedarray transducer for breast MRgHIFU treatments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, simulations of a breast-specific cylindrical ultrasound phased-array were performed on a breast model and initial phantom experiments were completed using a cylindrically mounted single solid transducer that was mechanically rotated. 18,19 The first laterally shooting HIFU transducer system to be used in malignant tissue on a patient 9 was not used beyond the initial feasibility study. A recent report 20 described a laterally shooting 384-element phasedarray transducer for breast MRgHIFU treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49] However, the literature does not have many reports on the use of a linefocused acoustic device for thermal therapy except for a 1990 patent by Lele, who proposed it for hyperthermia applications (nonablative temperatures), and the more recent development of slightly focused curvilinear applicators for transurethral prostate thermal therapy. [50][51][52] Lele's patent mentioned the potential advantage of lower intensities afforded by line-focusing over point-focusing transducers.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observe that the circular ablation protocol was capable of coagulating a large region of tumor, with a rapid, 60-second treatment time and, when augmented with chemotherapy, was curative. Alternatively, the application of multiple treatment points in a grid is applied in the ExAblate clinical system (44,45) and from phased treatment arrays (46). Sequential treatment of multiple points requires rest periods for tissue cooling as well as frequent mechanical repositioning of the ultrasound transducer; therefore, we observed that a circular protocol provides substantial time savings in our model.…”
Section: Enhancement Persists Through Repeated Administration Of Mrg-mentioning
confidence: 94%